Colony Diet Influences Ant Worker Foraging and Attendance of Myrmecophilous Lycaenid Caterpillars - Pohl, Sebastian; Frederickson, Megan E.; Elgar, Mark A.; Pierce, Naomi E. (Frontiers in Ecology and Evolution, 2016)
Foraging animals regulate their intake of macronutrients such as carbohydrates and proteins. However, regulating the intake of these two macronutrients can be constrained by the nutrient content of available food sources. Compensatory foraging is a method to adjust nutrient intake under restricted nutrient availability by preferentially exploiting food sources that contain limiting nutrients. Here we studied the potential for compensatory foraging in the dolichoderine ant Iridomyrmex mayri, which is commonly found in associations with caterpillars of the obligatorily ant-associated lycaenid butterfly Jalmenus evagoras. The caterpillars receive protection against predators and parasites, and reward the ants with nutritional secretions from specialized exocrine glands. These secretions contain a mixture of sugars and free amino acids, particularly serine. We tested the influence of nutrient-deficient diets on foraging patterns in I. mayri by recording the intake of test solutions containing single types of macronutrients during food preference tests. We also investigated the level of ant attendance on fifth instar J. evagoras caterpillars to evaluate how changes in diet influenced ant tending of caterpillars and foraging on their secretions. Foragers on a protein diet compensated for the nutritional deficit by increasing the intake of test solutions that contained sucrose, compared to their counterparts on a non-restricted diet. Ants on a sugar diet, however, did not show a corresponding increased consumption of test solutions containing the amino acid serine. Additionally, compared with their counterparts on a mixed diet, ants on limited nutrient diets showed an increase in the number of caterpillar-tending workers, suggesting that the caterpillars’ secretions are suitable to compensate for the ants’ nutritional deficit.